Inactivation of TCA cycle enhances Staphylococcus aureus persister cell formation in stationary phase - Wang, Ying (Sci Rep, 2018)
Persister cells constitute a small subpopulation of bacteria that display remarkably high antibiotic tolerance and for pathogens such as Staphylococcus aureus are suspected as culprits of chronic and recurrent infections. Persisters formed during exponential growth are characterized by low ATP levels but less is known of cells in stationary phase. By enrichment from a transposon mutant library in S. aureus we identified mutants that in this growth phase displayed enhanced persister cell formation. We found that inactivation of either sucA or sucB, encoding the subunits of the α-ketoglutarate dehydrogenase of the tricarboxylic acid cycle (TCA cycle), increased survival to lethal concentrations of ciprofloxacin by 10–100 fold as did inactivation of other TCA cycle genes or atpA encoding a subunit of the F(1)F(0) ATPase. In S. aureus, TCA cycle activity and gene expression are de-repressed in stationary phase but single cells with low expression may be prone to form persisters. While ATP levels were not consistently affected in high persister mutants they commonly displayed reduced membrane potential, and persistence was enhanced by a protein motive force inhibitor. Our results show that persister cell formation in stationary phase does not correlate with ATP levels but is associated with low membrane potential.